A Bad Job of Doing Good: Does Corporate Transparency on a Country and Company Level Moderate Corporate Social Responsibility Effectiveness?. Issue 2 (June 2021) - Heinberg, Martin; Liu, Yeyi; Huang, Xuan; Eisingerich, Andreas B.
Numerous studies argue that corporate social responsibility (CSR) helps companies build strong and positive relationships with consumers. However, it is not well understood why certain companies are more effective in their CSR activities than others. Some studies have attributed this difference to the country setting, but results are inconclusive. Building on signaling theory, this study explores corporate transparency as a boundary condition of the effects of CSR activities on the consumer–brand relationship. Three experiments and one large survey across three countries examine how a lack of corporate transparency undermines firms' CSR efforts. Importantly, the authors theorize that country environments differ in terms of transparency, which is then reflected in different levels of corporate transparency. Different country levels of transparency help explain the discrepancies of CSR effectiveness for increasing brand attachment and building consumer behavior. Finally, the authors tie the diminishing effect of CSR in the case of low corporate transparency to an increase in consumer skepticism.